Chapter 14 Samhandling Under Risk Applying Concurrent Learning to Prepare for and Meet the Unforeseen - Steiro, Tryge. J. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"This chapter aims to examine how samhandling and concurrent learning work together. "Concurrent learning" is a form of simultaneous learning, where many learning processes related to samhandling take place at the same time. Samhandling and concurrent learning are also functional processes, in the sense that learning also occurs through daily interaction activities or actions. At the same time, concurrent learning and samhandling are interdependent and they are, therefore, in a sense part of the same process (hence concurrent learning). The chapter identifies five factors identified as important to samhandling and concurrent learning. These are: (1) Awareness of basic assumptions regarding people; relations and teamwork are essential; (2) Space, (3) Giving of themselves, (4) Making processes transparent and addressing problems as early as possible, and (5) Reflection as a key to samhandling and concurrent learning. Samhandling and concurrent learning represent a mindset, a way of working and a form of learning, which together help to meet and/ or develop the skills needed to tackle the challenges of flexible organizations."